Banana Endophytic Fungi Producing Antagonistic, Antioxidant, and Antibacterial Bioactive Metabolites - Aji, Oktira Roka; Putri, Diah Asta; Yuliani, Ririn Kholifatu; Ilma, Nur Malika; Astuti, Sutan Nur Chamida Tri (Universitas Djuanda, 2026)
The increasing prevalence of antibiotic-resistant pathogens and the environmental hazards associated with synthetic agrochemicals have intensified the search for natural bioactive agents. This study isolated and identified endophytic fungi from banana (Musa spp.) and evaluated their antimicrobial and antioxidant activities. Endophytic fungi were isolated from leaf and stem tissues using a surface-sterilization method, followed by culture purification. Antagonistic activity was assessed through dual culture assays, while molecular identification was performed using ITS rDNA sequencing. Five isolates were obtained, and isolate J2 exhibited clear antifungal activity against Fusarium oxysporum. Sequence analysis showed that J2 is closely related to Talaromyces aculeatus. Fungal metabolites were extracted using methanol and ethyl acetate, and the extracts were tested for antioxidant activity (DPPH assay), total phenolic content, and antibacterial activity against Escherichia coli and Bacillus cereus. The methanol extract exhibited stronger antioxidant activity (IC₅₀: 3285.41 ± 80.06 ppm), while the ethyl acetate extract showed higher phenolic content (45.04 ± 9.02 mg GAE/g) and superior antibacterial effects. These results highlight T. aculeatus as a promising natural source of multifunctional bioactive compounds.